Effects of diet density and feeding frequency during the rearing period on broiler breeder performance. Issue 5 (3rd September 2021) - van Emous, R. A.; Mens, A. J. W.; Winkel, A.
ABSTRACT: 1. An experiment was conducted to study the effects of diet density and feeding frequency during the rearing period on broiler breeder performance between three and 40 weeks of age. 2. A total of 960 female one-day-old chicks (Ross 308) were randomly allocated to 24 floor pens (12 pens in two rooms). On day 21 pullets were assigned to a 2 × 2 factorial arrangement including two diets (control (CON) or 16% diluted (DIL)) and two feeding strategies (fed once (FO) or twice (FT) a day). The FO pullets were fed at 0815 h (100%) and FT pullets at 0815 h (60%) and 1215 h (40%). Water was provided by nipple drinkers with drip cups during 7 and 8 h in the rearing and laying period, respectively. 3. Body weight (BW) and water intake were measured weekly and BW uniformity at 10 and 20 weeks of age. Litter characteristics were measured at 10, 15, and 20 weeks of age. During the laying period, egg production and incubation characteristics were recorded. 4. The DIL pullets received a higher feed allowance in combination with similar water intake which resulted in a lower water/feed ratio compared to the CON pullets resulting in a higher DM content of the litter and improved litter quality. The higher feed allowance resulted in a 20% higher total manure production at 20 weeks of age. The FT pullets showed a lower body weight (BW) CV at 10 weeks of age; however, no effect was found at 20 weeks of age. During the laying period, FT pullets tended to have earlier onset of lay, higher total egg production at 30 weeks of age and better fertility. 5. It was concluded that alternative feeding strategies can positively influence production performance during both the rearing and laying period.